Herders' perceptions on ruminant livestock breeds and breeding management in Southwestern Niger - Ayantunde, Augustine A.; Kango, M.; Hiernaux, Pierre H.Y.; Udo, H.M.J.; Tabo, Ramadjita (Springer, 2007)
This study documents indigenous knowledge of breeds of cattle, sheep and goats in southwestern Niger, and includes both pastoralists and agropastoralists. Our study included sheep and goats in view of the increasing importance of small ruminants in livestock production systems in the Sahel since the drought of the 1970s and 1980s. This study was carried out under the Desert Margins Program (DMP) project on arresting land degradation and the conservation of biodiversity in desert margins of sub-Saharan Africa, partly funded by the Global Environment Facility (GEF).